Study of Approaches of Educational Technology - Kumar, Rajesh (Innovative Research Thoughts, 2018)
Education is a very important and integral part of society that governs the social functioning. It deeply connects with the wants and ambitions of every society. This is the reason that education cannot remain unaffected by any social change that takes place around us. In general, there is active participation and involvement of radio, television, computers, machines, films, and now the Internet and multimedia, in providing education and educational material to students. Smartboards, personal laptop computers, online classrooms, video technologies, and projection equipment have all been implemented in the classroom throughout time. The use of technology in classrooms is fraught with controversy. Some argue that technology is a distraction in the classroom.